A functional variant in the OAS1 gene is associated with Sjögren's syndrome complicated with HBV infection. Issue 1 (December 2017) - Liu, Xianjun; Xing, Hongcun; Gao, Wenjing; Yu, Di; Zhao, Yuming; Shi, Xiaoju; Zhang, Kun; Li, Pingya; Yu, Jiaao; Xu, Wei; Shan, Hongli; Zhang, Kaiyu; et al.
Abstract Hepatitis B virus (HBV) has been suspected to contribute to several autoimmune diseases, including Sjögren's syndrome (SS), although the exact mechanism is unknown. The 2′–5′ oligoadenylate synthetase (OAS1) is one of the most important components of the immune system and has significant antiviral functions. We studied a polymorphism rs10774671 of OAS1 gene in Han Chinese descent. The minor allele G was significantly associated with a decreased risk for SS, anti-SSA-positive SS, and anti-SSA-positive SS complicated with HBV infection, which have not been seen in anti-SSA-negative SS and HBcAb-negative SS patients. Gene expression analysis showed that the risk-conferring A allele was correlated with lower expression of p46 and increased expression of p42, p48, and p44. A functional study of enzymatic activities revealed that the p42, p44, and p48 isoforms display a reduced capacity to inhibit HBV replication in HepG2 cells compared to the normal p46 isoform. Our data demonstrated that the functional variant, rs10774671, is associated with HBV infection and anti-SSA antibody-positive SS. The SAS variant switches the primary p46 isoform to three alternatives with decreased capacities to inhibit HBV replication. These data indicated that individuals harboring the risk allele might be susceptible to hepatitis B infection and SS development.